2016
DOI: 10.5455/javar.2016.c177
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and antibiogram of Salmonella spp. from duck and pigeon in Dinajpur, Bangladesh

Abstract: Objective: This research work was conducted for isolation of Salmonella spp. from duck and pigeon and assessment of antibiotic sensitivity patterns of the isolated Salmonella spp. Materials and methods: A total of 48 duck samples comprising of liver (n=16) spleen (n=16) and intestinal content (n=16) were collected from 16 ducks (8 sick and 8 dead). Similarly, 42 pigeon samples comprising of liver (n=14), spleen (n=14) and intestinal contents (n=14) were collected from 14 pigeons (7 sick and 7 dead). The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…In quail isolates, 60% resistance to Florphenicol and the lowest percentage was 20% to Nalidixic acid, Flumequin, Oxytetracyclin and Sulfamethoxazole/ Trimethoprim while Ciprofloxacin, Enerofloxacin, Norfloxacin, Levofloxacin Cefotaxime, Ceftriaxone, Ceftazidime, Neomycin, Amikacin and Gentamycin showed sensitivity with 100% but Florphenicol was the lowest sensitivity with percentage of 40%. The results in this study nearly in coordinated with Rahman et al, (2011) anddiffer from Bacci et al, (2012) who reported that the isolated Salmonellae from quails exhibited 89.2% resistance to Sulfamethoxazole and 24.3% to Ampicillin, Gentamicin, Sulfamethoxazole and Tetracycline in addition to Helm et al, (1999) who reported that Salmonella typhimurium isolated from bobwhite quail was resistant to Ampicillin, Chloramphenicol, Sulfonamides, and Tetracycline.…”
Section: Discussionsupporting
confidence: 89%
“…In quail isolates, 60% resistance to Florphenicol and the lowest percentage was 20% to Nalidixic acid, Flumequin, Oxytetracyclin and Sulfamethoxazole/ Trimethoprim while Ciprofloxacin, Enerofloxacin, Norfloxacin, Levofloxacin Cefotaxime, Ceftriaxone, Ceftazidime, Neomycin, Amikacin and Gentamycin showed sensitivity with 100% but Florphenicol was the lowest sensitivity with percentage of 40%. The results in this study nearly in coordinated with Rahman et al, (2011) anddiffer from Bacci et al, (2012) who reported that the isolated Salmonellae from quails exhibited 89.2% resistance to Sulfamethoxazole and 24.3% to Ampicillin, Gentamicin, Sulfamethoxazole and Tetracycline in addition to Helm et al, (1999) who reported that Salmonella typhimurium isolated from bobwhite quail was resistant to Ampicillin, Chloramphenicol, Sulfonamides, and Tetracycline.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the variation of isolation rates in different localities may be due to the prophylactic and therapeutic use of antibiotics, vaccination against viruses and immune status of ducklings or variation in degree of hygiene and overloading in the farms. Regarding to the phenotypic characters of isolated Salmonella, the colonial appearance and the biochemical profile were similar to those previously reported such as the fermentation of certain sugars or enzymatic reaction that might be characteristic of highly virulent strains associated with Salmonellosis (Markey et al, 2013;Rahman et al, 2016;Ahmed et al, 2019). Moreover, the serogroups obtained Table (3 Fimbriae play an important role in the pathogenicity of bacteria, because they promote their attachment to intestinal epithelial cells and encoded by the pef operon located in plasmid (Castilla et al, 2006).Similar findings of plasmid encoded fimbriae (pefA) gene (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Salmonella was isolated from turkey in Dakahlia Governorate in Egypt with a percentage of (10%) and these results nearly in coordinated with Tel et al, (2013) who detected Salmonella with a percentage of (9.7%). Salmonella was isolated from quails in Port Said Governorate in Egypt with a percentage of (10%) (5 out of 50 examined quails) and these results differ from Zlem et al, (2002) who isolated seven Salmonellae from 123 whole quail eggs with incidence of (5.69%), while Mukhopadhayay (2007) who isolated Salmonella from liver and heart of 128 Japanese quails with an incidence of 1.6% and Rahman et al, (2011) who isolated Salmonella from quail in Bangladesh form liver, spleen and intestine with an incidence of 29.62%. Salmonella was isolated from pigeons in Dakahlia Governorate in Egypt with a percentage of (6.7%) (2 out of 30 examined pigeons) and these results nearly in coordinated with González-Acuña et al, (2007) who isolated Salmonella from pigeons with a percentage of (4%) and Rahman et al, (2011) isolated Salmonella from pigeons in Bangladesh form liver, spleen and intestine with an incidence of 26.66%.…”
Section: Discussionmentioning
confidence: 66%